Isokinetic concentric quadriceps and hamstring strength variables from the NFL scouting combine are not predictive of hamstring injury in first-year professional football players - Zvijac, J. E.; Toriscelli, T. A.; Merrick, S.; Kiebzak, G. M. (The American Journal of Sports Medicine, 2013)
Background: There are conflicting reports regarding the association between isokinetic concentric quadriceps and hamstring strength deficits and ratios and risk for hamstring injuries in athletes.